Novel CAPN3 variant associated with an autosomal dominant calpainopathy. (10th June 2020) - Cerino, M.; Campana‐Salort, E.; Salvi, A.; Cintas, P.; Renard, D.; Juntas Morales, R.; Tard, C.; Leturcq, F.; Stojkovic, T.; Bonello‐Palot, N.; Gorokhova, S.; Mortreux, J.; et al.
Abstract : Aims: The most common autosomal recessive limb girdle muscular dystrophy is associated with the CAPN3 gene. The exclusively recessive inheritance of this disorder has been recently challenged by the description of the recurrent variants, c.643_663del21 [p.(Ser215_Gly221del)] and c.598_612del15 [p.(Phe200_Leu204del)], associated with autosomal dominant inheritance. Our objective was to confirm the existence of autosomal dominant calpainopathies. Methods: Through our activity as one of the reference centres for genetic diagnosis of calpainopathies in France and the resulting collaborations through the French National Network for Rare Neuromuscular Diseases (FILNEMUS), we identified four families harbouring the same CAPN3 heterozygous variant with supposedly autosomal dominant inheritance. Results: We identified a novel dominantly inherited CAPN3 variant, c.1333G>A [p.(Gly445Arg)] in 14 affected patients from four unrelated families. The complementary phenotypic, functional and genetic findings correlate with an autosomal dominant inheritance in these families, emphasizing the existence of this novel transmission mode for calpainopathies. The mild phenotype associated with these autosomal dominant cases widens the phenotypic spectrum of calpainopathies and should therefore be considered in clinical practice. Conclusions: We confirm the existence of autosomal dominant calpainopathies as an entity beyond the cases related to the in‐frame deletions c.643_663del21 and c.598_612del15, with the identification of a novel dominantly inherited and well‐documented CAPN3 missense variant, c.1333G>A [p.(Gly445Arg)]. In addition to the consequences for genetic counselling, the confirmation of an autosomal dominant transmission mode for calpainopathies underlines the importance of re‐assessing other myopathies for which the inheritance is considered as strictly autosomal recessive.